2008
DOI: 10.1007/s11095-008-9765-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of PSC-RANTES for HIV-1 Prevention using Biodegradable Nanoparticles

Abstract: Purpose Nanoparticles formulated from the biodegradable co-polymer poly(lactic-co-glycolic acid) (PLGA), were investigated as a drug delivery system to enhance tissue uptake, permeation, and targeting for PSC-RANTES anti-HIV-1 activity. Materials and Methods PSC-RANTES nanoparticles formulated via a double emulsion process and characterized in both in vitro and ex vivo systems to determine PSC-RANTES release rate, nanoparticle tissue permeation, and anti-HIV bioactivity. Results Spherical, monodisperse (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 57 publications
4
93
1
2
Order By: Relevance
“…PLGA-based encapsulation of nanoparticles is widely used for drug delivery because of its biodegradability, allowing its reabsorption by the body and, hence, lowering toxicity (83). PLGA nanoparticles have been demonstrated to intravaginally deliver small interfering RNA (siRNA) and Rantes (58,81). Therefore, the incorporation of nanoparticle encapsulation into a microbicide formulation has the potential to confer long-term protection from a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA-based encapsulation of nanoparticles is widely used for drug delivery because of its biodegradability, allowing its reabsorption by the body and, hence, lowering toxicity (83). PLGA nanoparticles have been demonstrated to intravaginally deliver small interfering RNA (siRNA) and Rantes (58,81). Therefore, the incorporation of nanoparticle encapsulation into a microbicide formulation has the potential to confer long-term protection from a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for developing alternative vaginal drug delivery systems for application as microbicides. Temperatureand pH-sensitive hydrogels and nanoparticles are currently being explored as potential microbicide delivery systems (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…41 However, in other studies, PLA NPs were demonstrated to be feasible drug delivery carriers to enhance tissue uptake and the targeting of other macromolecules with anti-HIV-1 activity. 42 Also, PLGA nanoparticles have shown interesting applications as vaccine-delivery vehicles for treatment of viral infections. 43 Polyhexylcyanoacrylate nanoparticles were loaded with saquinavir (another HIV protease inhibitor) or zalcitabine (a nucleoside analog) and tested under in vitro conditions in primary human monocytes/macrophages.…”
Section: Antiviral Drugsmentioning
confidence: 99%